Quality of life in patients with locally advanced metastatic breast cancer after palliative treatment - O. Bondar (Journal of Education, Health and Sport)
The majority of scientists obtain subjective data by patients surveying using questionnaire. More than 400 different general and special questionnaires have been proposed and used to assess the quality of life in modern oncology. The purpose of the study was to evaluate the quality of life in the fields of mental and physical conditions of patients with metastatic breast cancer who underwent palliative surgery compared with patients who received standard treatment regimens, and to determine the level of satisfaction with social relationships. Due to quality of life concept multifactorial nature the questionnaire takes into account three main aspects: physical (medical), psychological and social. The data obtained allow to state that breast cancer patients quality of life self-perception depends on the methods of treatment used: intra-arterial polychemotherapy, radiotherapy, hormone therapy, bisphosphonate therapy and palliative surgery. In the areas of mental and physical condition, the quality of life was higher in patients in the experimental group than in patients in the control group, where they received standard treatment without surgery.